2012
DOI: 10.1007/s00192-012-1666-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of preoperative examination and magnetic resonance imaging for diagnosis of anterior vaginal wall masses

Abstract: Preoperative diagnosis using exam, MRI, and cystourethroscopy have a high diagnostic accuracy for anterior vaginal wall masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
1
0
2
Order By: Relevance
“…However, the utility of imaging extends beyond establishing a diagnosis as it delineates the anatomical configuration of the mass, making it a valuable tool for surgical planning and patient counseling 10 . Though the latter study found 100% sensitivity for MRI diagnosis of UD, 12 the overall accuracy found in our study (75.6%) aligns with other previous studies (70%–79%) 13–15 . This study supports MRI in differentiating underlying etiologies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the utility of imaging extends beyond establishing a diagnosis as it delineates the anatomical configuration of the mass, making it a valuable tool for surgical planning and patient counseling 10 . Though the latter study found 100% sensitivity for MRI diagnosis of UD, 12 the overall accuracy found in our study (75.6%) aligns with other previous studies (70%–79%) 13–15 . This study supports MRI in differentiating underlying etiologies.…”
Section: Discussionsupporting
confidence: 87%
“…10 Though the latter study found 100% sensitivity for MRI diagnosis of UD, 12 the overall accuracy found in our study (75.6%) aligns with other previous studies (70%-79%). [13][14][15] This study supports MRI in differentiating underlying etiologies. Another utility of MRI may be in the follow-up of patients postoperatively, especially in patients with malignant or pre-malignant lesions.…”
Section: Discussionsupporting
confidence: 76%
“…The size and complexity of a urethral diverticulum and its relationship to surrounding anatomy on MRI can affect surgical management [43][44][45]. The distinction between a urethral diverticulum and a Skene gland cyst or a vaginal wall cyst alters the surgical approach, and risk of complication, and can be made in most cases with MRI [46][47][48]. (See Variants 1-4.…”
Section: Urinary Dysfunctionmentioning
confidence: 98%
“…По литературным данным, одним из самых высокоинформативных исследований при визуализации этой анатомической области является магнитно-резонансная томография (МРТ) с контрастированием. МРТ, как и трансвагинальное ультразвуковое исследование (УЗИ), успешно используется при визуализации кист и дивертикулов уретры у женщин, а также при оценке степени спонгиофиброза при стриктурах у мужчин [21,[29][30][31][32][33][34][35][36]. Этот метод позволяет детально визуализировать патологические изменения мочеиспускательного канала и вокруг расположенных тканей, и может быть использован в качестве дополнительной неинвазивной диагностики при указанных заболеваниях.…”
unclassified